Upaya Penataan Lingkungan Sosial dan Ekonomi Pedagang Kaki Lima di Kota Surakarta Berdasarkan Tipologi Lokasi Stabilisasi Surakarta - Murtanti Jani Rahayu; Imam Buchori; Retno Widjajanti (Jurnal Wilayah dan Lingkungan, 2020)
The street vendors (SVs) select the trading locations according to the activity characteristics. The selected locations are often located in the areas of public facilities or state-owned lands which are all at once close to productive main activities. This way is aimed to drive many people to come and buy their goods after doing certain main activities. In addition, street vendors tend to choose trading locations on highways having vast social activities. The Surakarta City Government has controlled street vendors through structuring in the form of stabilization and relocation. This study aims to identify changes in the social and economic environment of street vendors based on the typology of street vendor stabilization locations in Surakarta. This study used a qualitative descriptive analysis to analyze changes in the social and economic environment with the typology of street vendor stabilization locations in Surakarta. The setting location typologies were determined based on the characteristics of street vendors’ stabilization locations viewed from the proximate main activities. The results of study showed that there were three typologies of stabilization locations, namely the locations approaching trading areas, settlement, and recreation. The operating hours of the street vendors depended on the proximate main activities. The street vendors in the settlement areas tended to open earlier and end their activities later at night than the street vendors proximate to the trade and recreation areas. The street vendors' capital starts at ≤ Rp. 500,000 to > Rp. 3,000,000. The street vendors with small capital usually trade longer than the street vendors with large capital. The street vendors with large capital are most often found trading at night.